Moral and patriotic coordinates of volunteer activity as a means of building educational and socio-pedagogical work - Zozuliak-Sluchyk, Rоksoliana; Yurchenko, Liubov; Onypchenko, Oksana; Bilozerova, Marianna; Vorovka, Marharyta (My University, 2022)
In the article, the built picture of the four-vector phenomenology of voluntary activity (heroic, victim, transformative, life-affirming) can serve as a kind of “ethical map” for measuring the motivation for participation in volunteering. In addition, it can serve as the basis for determining the goals and mission of building educational and socio-pedagogical work in various volunteer associations. The problem of the formation of social activity of student youth in the conditions of reforming Ukrainian society is analyzed, the criteria of social activity, the importance of social activity for the further development of society and the professional development of students are considered. The concept of volunteering as a segment of civil society, the main directions of volunteering in modern Ukraine, the impact of hostilities in the East of the country on the development of volunteering have been studied. The thesis about the dialectical relationship between social activity and students' participation in volunteer activities is substantiated, where volunteer activity is considered as a manifestation of social activity and as a factor in its formation. An example of the activities of a higher educational institution regarding the involvement of students in volunteer practice as an important factor in the formation of students' social activity is given
Keywords: patriotic; volunteer activity; Socio-Pedagogical Work; educational process; патріотизм; волонтерська діяльність; соціально-педагогічна робота; освітній процес